Feeding Ecology of Sloth Bears in Chitwan National Park, Nepal - Khanal, Sandip; Thapa, Tej B. (Journal of Institute of Science and Technology, 2015)
Food habits of a species influences habitat use, ranging pattern and behavior. Seasonal diet composition of Sloth bear (Melursus ursinus) in the Chitwan National Park, Nepal was determined from 143 scats. Through macroscopic and microscopic analysis of scats; six types of plants, termites, ants, honey bees, wax, as well as mammalian hairs were identified. Although variation was observed, there was no significant difference in the diet composition in two different seasons. Overall, insects dominated the composition, occurring in 100% of the scats followed by the plants (39.16%) and mammalian hair (3.49%). Termites and ants were the major and stable dietary components. Termites (90%), Red ants (65%) and Aegle marmelos (35%) were important food for Sloth bear in summer season but the utilization of plants was very low. During winter, insects were heavily utilized by the bear. The utilization of termites (93.97%) and Ziziphus sp. (14.45%) was higher in comparison with summer season. Utilization of fruits in summer was negligible. By and large, on percent dry weight basis, insects (78.98%) dominated Sloth bear diet, followed by plants (20.99%) and mammalian hairs (0.04%). Journal of Institute of Science and Technology, 2014, 19(2): 118-122